The Effect of Entrepreneurship Orientation, Knowledge Management, and Partnership on MSMEs Performance in the Perspective of the Islamic Economy with Competitive Advantage as an Intervening Variable - Lubis, Aulia Nurrahmah; Batubara, Maryam; Bi Rahmani, Nur Ahmadi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This research aims to know the influence of entrepreneurial orientation toward competitive advantage, to determine the effect of management knowledge on competitive advantage, the effect of partnership on competitive advantage, entrepreneurial orientation on the performance of MSMEs, management knowledge on the performance of MSMEs, partnership on the performance of MSMEs, competitive advantage on the performance of SMEs, entrepreneurial orientation on the performance of MSMEs through competitive advantage, management knowledge on the performance of MSMEs through competitive advantage, partnerships on the performance of MSMEs through competitive advantage. The type of research that will be carried out in this study is quantitative research. Results of the research show that entrepreneurial orientation influences competitive advantage. Management knowledge influences competitive advantage. The partnership has no effect on competitive advantage. Entrepreneurial orientation influences the performance of MSMSe. Management knowledge influences the performance of MSMEs. The partnership has no effect on the performance of MSMEs. Competitive advantage has no effect on the performance of MSMEs. Entrepreneurial orientation influences the performance of MSMEs through competitive advantage. Management knowledge has no effect on the performance of MSMEs through competitive advantage. The partnership does not affect the performance of MSMEs through competitive advantage.